Shaping Archaeological Archives - Raja, Rubina (Brepols, 2023)
Archaeology as a discipline has undergone significant changes over the past decades, in particular concerning best practices for how to handle the vast quantities of data that the discipline generates. Much of this data has often ended up in physical - or, more recently, digital - archives and been left untouched for years, despite containing critical information. But as many recent research projects explore how best to unleash the potential of these archives through publication, digitization, and improved accessibility, attention is now turning to the best practices that should underpin this trend. In this volume, scholars turn their attention to how best to work with and shape archaeological archives, and what this means for the field as a whole. The majority of case studies here explore archaeological sites in the eastern Mediterranean and the Middle East, some of which are conflict zones today. However, the contributions also showcase more broadly the depth of research on archaeological archives as a whole, and offer reflections upon the relationship between archaeological practices and archival forms. In so doing, the volume is able to offer a unique dialogue on best practices for the dissemination and synthetization of knowledge from archives more generally, whether physical or digital.